ANALISIS KEBUTUHAN TENAGA PERAWAT DENGAN METODE WORKLOAD INDICATOR STAFFING NEED (WISN) DI RUANG INTERNA INSTALASI RAWAT INAP RSD Dr. SOEBANDI JEMBER - Abu Khoiri; Dyah Kusworini; Ari Purwanto (Jurnal Ilmu Kesehatan Masyarakat, 2015)
Nursing services in the hospital for 24 hours a day, that have constant contact with the patient. Therefore, the nursing services at the hospital is an integral part of health care and contribute highly to determine the quality of hospital services. Based on patient data visit of Inpatient Installation of RSD Dr. Soebandi Jember which have increased from year to year, especially the highest number at interna unit. So that the necessary studies to calculate the optimal needs of nurses in the internal ward inpatient installation by the WISN (Workload Indicator Staffing Need) method .